Development of Google Form-Based Five-Tier E-Diagnostic Test to Identify Conception Levels and Track Students' Misconceptions on Thermodynamics Materials - Alifia Royani; Woro Setyarsih (IKIP Mataram, 2022)
The learning process can not be separated from the assessment activities. Google form is one of the assessment applications used during Covid-19 pandemic. In learning physics, students often have difficulty understanding concepts, leading to misconceptions. Student interview results showed that thermodynamics is a complex material. This research aims to develop a five-tier diagnostic test based on google form to identify the conception levels and track misconceptions in thermodynamic material. Research & Development method with eight stages, namely potential and problems, information gathering, instrument design, design validation, design revision, trial, instrument revision, and research test, was applied to obtain the instrument. The feasibility of the test was met by the results of validity and reliability tests. A total of 12 questions were successfully developed and declared valid and reliable at the value of 0.601. The research sample consisted of 47 students of 11th Grade of MAN 1 Bojonegoro. The results showed that the google form-based five-tier e-diagnostic test developed was able to identify conception levels and track students' misconceptions on thermodynamic material. The highest conception levels were dominated by Lack of Knowledge and the presence of misconceptions reached 28.33% in low category. Students' misconceptions are caused by wrong reasoning, intuition, humanistic thinking, preconceptions, and associative thinking. This five-tier diagnostic instrument can be used by physics teachers as an assessment instrument in physics learning. In addition, to fulfilling the evaluation and assessment objectives achievement, this instrument provides convenience in implementation, documentation, and track the causes of students' difficulties in understanding thermodynamic concepts.